Performance of Black and Indigenous applicants in a medical school admissions process - Girgulis, Katherine; Rideout, Andrea; Rashid, Mohsin (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2021)
Background: Diversity in medical schools has lagged behind Canada’s growing multicultural population. Dalhousie medical school allows Black and Indigenous applicants to self-identify. We examined how these applicants performed and progressed through the admissions process compared to Other group (applicants who did not self-identify).Methods: Retrospective analysis of four application cycles (2015-2019) was conducted, comparing demographic data, scores for application components (Computer-Based Assessment for Sampling Personal Characteristics (CASPer), MCAT, GPA, supplemental, discretionary, Multiple Mini Interview (MMI)), and final application status between the three groups.Results: Of 1322 applicants, 104 identified as Black, 64 Indigenous, and 1154 Other. GPA was higher in the Other compared to the Indigenous group (p < 0.001). CASPer score was higher in the Other compared to the Black group (p = 0.047). There was no difference between groups for all other application components. A large proportion of Black and Indigenous applicants had incomplete applications. Acceptance rates were similar between all groups. Black applicants declined an admission offer substantially more than expected (31%; p < 0.001).Conclusions: Black and Indigenous applicants who completed their application progressed well through the admissions process. The pool of diverse applicants needs to be increased and support provided for completion of applications. Further study is warranted to understand why qualified applicants decline acceptance.